Waves of revolution. - India Students Association:::Creator::::::::::::
Promotional poster for a viewing of the short film "Waves of Revolution," directed by Anand Patwardhan depicting the Bihar movement, a revolution in India that challenged the existing power structure and attempted to establish a grassroots democracy.